2013
DOI: 10.1007/s12291-013-0319-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality Impact on Diagnostic Blood Specimen Collection Using a New Device to Relieve Venipuncture Pain

Abstract: A new device called Buzzy Ò has been recently presented that combines a cooling ice pack and a vibrating motor in order to relieve the venipuncture pain. The aim of this study was to evaluate the impact of Buzzy Ò use during diagnostic blood specimen collection by venipuncture for routine immunochemistry tests. Blood was collected from 100 volunteers by a single, expert phlebotomist. A vein was located on the left forearm without applying tourniquet, in order to prevent any interference from venous stasis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Twenty‐gage diameter IV catheter, EDTA K2 tube and Vacutainer™ are commonly used along with certified systems (Lima‐Oliveira et al., 2013, 2015). VIA scale is a validated classification of the peripheral venous system in terms of vascular access.…”
Section: The Studymentioning
confidence: 99%
“…Twenty‐gage diameter IV catheter, EDTA K2 tube and Vacutainer™ are commonly used along with certified systems (Lima‐Oliveira et al., 2013, 2015). VIA scale is a validated classification of the peripheral venous system in terms of vascular access.…”
Section: The Studymentioning
confidence: 99%
“…15 However, there was a higher success rate of the procedure at the first attempt with the Buzzy device reported by Baxter et al 11 There was a reported concern about the effect of cold vibration Buzzy on the reported blood levels of transferrin, proteins, albumin, hemoglobin, hematocrit, and erythrocytes. 22,23 Our attempts to ascertain the clinical significance of these alterations in the pediatric emergency setting were limited because these tests were not clinically indicated in a significant proportion of our cohort. The results of these tests often came as part of the general workup (eg, complete blood count as part of the workup for infection or complete metabolic panel for organ function) and did not modify the clinical decision-making, indicating that the concern about these parameters might not be of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…There were no anticipated adverse events with using the Buzzy device apart from the concern of false high protein, albumin and transferrin, erythrocytes, hemoglobin, and hematocrit levels. 22,23 The benefits of the anticipated outcome outweigh the possible effects of the stated tests, particularly in a busy ED. However, the treating physician was alerted for such possibilities to be considered and then if the clinical decision would be affected.…”
Section: Safetymentioning
confidence: 99%
“…In the present study, the control of confounding factor is questionable. The control of venipuncture pain and hemolysis which is an important primary inference on blood cortisol level should be considered (Lima-Oliveira et al 2013; Snyder et al 2004) and there is a remained question on the present study by Ahmed et al (Ahmed et al 2016) on the mentioned confounding factor. In clinical chemistry laboratory diagnostic test, the aberration of cortisol level can be seen in case with venipuncture pain and hemolytic samples (Lima-Oliveira et al 2013; Snyder et al 2004).…”
mentioning
confidence: 80%